2015
DOI: 10.1098/rsif.2015.0216
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput detection of ethanol-producing cyanobacteria in a microdroplet platform

Abstract: Ethanol production by microorganisms is an important renewable energy source. Most processes involve fermentation of sugars from plant feedstock, but there is increasing interest in direct ethanol production by photosynthetic organisms. To facilitate this, a high-throughput screening technique for the detection of ethanol is required. Here, a method for the quantitative detection of ethanol in a microdroplet-based platform is described that can be used for screening cyanobacterial strains to identify those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 28 publications
(36 reference statements)
0
57
0
Order By: Relevance
“…In fact, we have utilized this platform to successfully characterize the growth profile of a green microalga Tetraselmis suecica , and the lipid production in the colony‐forming green microalga Botryococcus braunii (Kim et al., ). In addition, previous studies using droplet microfluidics showed that cyanobacterial and microalgal species including C. reinhardtii, Chlorella , Neochloris , Synechocystis , and Dunaliella are amenable to droplet‐based studies (Abalde‐Cela et al., ; Dewan, Kim, McLean, Vanapalli, & Karim, ; Pan et al., ). In conclusion, lab‐on‐chip methods are beginning to realize their potential to revolutionize genetic screens in unicellular eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we have utilized this platform to successfully characterize the growth profile of a green microalga Tetraselmis suecica , and the lipid production in the colony‐forming green microalga Botryococcus braunii (Kim et al., ). In addition, previous studies using droplet microfluidics showed that cyanobacterial and microalgal species including C. reinhardtii, Chlorella , Neochloris , Synechocystis , and Dunaliella are amenable to droplet‐based studies (Abalde‐Cela et al., ; Dewan, Kim, McLean, Vanapalli, & Karim, ; Pan et al., ). In conclusion, lab‐on‐chip methods are beginning to realize their potential to revolutionize genetic screens in unicellular eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Our method enables detection in samples of concentration up to 70 g¨L´1 without dilution. Compared to another existing enzymatic droplet microfluidic method [31], our method is characterized in detail and optimized, which makes it potentially useful in research on different aspects of fermentation processes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Abalde-Cela et al [31] showed a microdroplet platform for detection of ethanol-producing cyanobacteria with the use of above described enzyme assay consisted of AOX and HRP. They used Amplex Red (AR) which reacts with hydrogen peroxide and forms the fluorescent molecule, resorufin.…”
Section: Introductionmentioning
confidence: 99%
“…Droplets act as segmented flow reactors that use an immiscible fluid to divide the reagent phase into discrete parts with an equal volume . Besides, the addition of reagent can be done merely by inserting a side‐channel anywhere along with the main channel . Droplet flow has another significant advantage over continues flow: since the reaction mixture is away from the channel walls, any reaction products that might deposit there (solids, sticky gels, etc.)…”
Section: Introductionmentioning
confidence: 99%